The impact of banking governance on achieving financial stability within the Algerian banking system: an analytical study of the Bank of Algeria for the period (2014-2021) - achouri, Badreddine; taibi, hamza (Journal of Research in Finance and Accounting, 2023)
This study aims to highlight the impact of banking governance on achieving financial stability by conducting an analytical study of the Bank of Algeria during the period (2014-2021) and addressing the various aspects that enhance financial stability within the banking system. The study concluded that the solvency ratios of the banking sector exceeded the minimum requirements of the prudential rules recommended under Basel III, especially in terms of Tier 1 capital and total solvency. The state ownership of most of the banks operating in Algeria hinders transparent competition among them, which often leads to financial instability in the banking system. Therefore, the Bank of Algeria must play its role in enhancing financial stability by issuing regulations and regulatory rules and imposing supervisory oversight on banks' operations